Sistem Komputerisasi Pengolahan data Penjualan dan Stok Pada Distributor alat alat Listrik - Budi Hartono; Iwan Koerniawan; Ahmad Ashifuddin Aqham (Universitas Sains dan Teknologi Komputer, 2020)
In line with the development of science and technology today, a job that is done requires fast-paced data and information. By getting data and information quickly, the company has the ability to develop faster. Inventory is a very important part for a company. Inventory of goods is one of the tasks of logistics management in a company, namely support in the procurement of goods for the company. In order for this support to be utilized, it is necessary to plan and carry out in an integrated manner, which is interrelated and supports between related elements. CV Sinar Karya Ungaran is a private company which is engaged in the distributor of Electric tools. CV Sinar Karya is located on the road Dabo II / D30 RT6 Nitibuana, Ungaran Regency Semarang Tel. (024) 3584074 - 3584075. This company has a wide enough working area covering Central Java and DIY. Because the working area is quite extensive and the number of processes in and out of goods, the company must be more careful in calculating inventory. In the process of recording and counting inventory at this time the company is still using Microsoft Excel so there are still many obstacles. In the process of recording and counting inventory at this time the company still uses Microsoft Excel. One of the difficulties experienced is the frequent occurrence of errors in making inventory reports. Besides making reports takes longer because there is no computerized database system. With the development of technology, especially in the field of computers, the authors try to create a computer-based inventory program using Visual Basic 6.0. This is expected to help companies in making goods inventory more quickly and accurately.